A NON LINEAR ANALYSIS OF STRUCTURE: PUSHOVER ANALYSIS - NEHA OSWAL; VIJAY V. SHINDE (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper we propose to assess seismic performance of a six stored reinforced concrete building designed according to the Moroccan seismic code RPS2000[1].the building is residential and has a reinforced concrete frame structural system. In the first time a set of dynamic analysis are carried out to compute dynamic properties of the building (fundamental period, natural frequencies, deformation modes), in the second time a pushover analysis is performed to assess the seismic performance of the building and detect the locations of the plastic hinges. Pushover analysis was performed using SAP2000.the results obtained from this study show that designed building perform well under moderate earthquake, but is vulnerable under severe earthquake.